2019
DOI: 10.1371/journal.pone.0226614
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis among adult males with a history of male-to-male sexual contact living with diagnosed HIV in New York State (excluding New York City): The challenge of intersecting epidemics

Abstract: Since 2009, syphilis has been increasing in New York State (NYS) excluding New York City (NYC) among men with a history of male-to-male sexual contact (MSM). Because MSM make up a disproportionate number of new HIV infections, this study aims to: 1) establish yearly rates of early syphilis diagnosis, 2) assess factors associated with early syphilis diagnosis, and 3) describe missed opportunities for earlier diagnosis of syphilis among MSM living with diagnosed HIV(MSMLWDH) in NYS, excluding NYC. A cohort of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…9 Among MSM LWH in New York State, the prevalence from 2013–2016 was 2.2%. 10 Another study of PLWH in several US cities found an incidence rate of 0.8 cases per 100 person-years between 2005–2016, with higher rates among MSM. 19 In the District of Columbia (DC)Cohort Longitudinal Study, 55 + PLWH had 0.5% prevalence and an incident rate of 0.2 per 100 person years from 2011 to 2015, with higher rates in Hispanic individuals.…”
Section: Resultsmentioning
confidence: 99%
“…9 Among MSM LWH in New York State, the prevalence from 2013–2016 was 2.2%. 10 Another study of PLWH in several US cities found an incidence rate of 0.8 cases per 100 person-years between 2005–2016, with higher rates among MSM. 19 In the District of Columbia (DC)Cohort Longitudinal Study, 55 + PLWH had 0.5% prevalence and an incident rate of 0.2 per 100 person years from 2011 to 2015, with higher rates in Hispanic individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the sexual dysfunction in HIV-infected men could be further enhanced by STDs recurrences, which are also directly related to infertility and subfertility [ 174 , 190 ]. Indeed, co-infection with multiple pathogens is common worldwide in people living with HIV [ 191 , 192 , 193 , 194 , 195 ]. Among these, several SDTs could lead to physical consequences, both anatomical, hormonal and neurological, which can further aggravate sexual dysfunction.…”
Section: Impact Of Fertility Concern and Diseases Of The Seminalmentioning
confidence: 99%
“…Studies of reported outbreaks in recent years explain the high incidence in young people with their lifestyles and harmful practices that predispose to the spread of the infection (unprotected sex, drug and alcohol use, HIV-positive status, etc.) (10,12,13). Increasing cases of women of reproductive age also increase the risk of congenital syphilis.…”
Section: Discussionmentioning
confidence: 99%